Determinação de curva glicolítica em carcaças de aves PSE (Pale, soft, exsudative) e normal em linha de abate industrial - Kaiser, Tania Regina (2016)
Some quality defects can cause changes in attributes of the meat, among these we can detach the PSE meat (Pale, Soft and Exudative). The PSE meat is pale, flaccid and exudative and result from sudden pH decrease while the carcass is still under high temperature. The identification of PSE meat has been done by measuring pH and L* (Lightness). However, studies suggest that a more precise evaluation of the kinetics of pH and temperature decrease has to be conducted to better understand the etiology of PSE meat in poultry. The aim of this study was to obtain the glycolytic curve for normal and PSE meat of chicken, through the pH, L* and CRA (water holding capacity) analysis. This experiment was conducted with carcasses obtained from a commercial slaughterhouse (n = 35) of Cobb lineage, 50 days old, from the same batch of creation and with the same pre-slaughter fasting time (10h). Samples of breast fillets were obtained from carcasses randomly collected immediately at the output of pre-cooling chiller, and the analysis of pH, temperature and L * were conducted in the same in times 1h35, 2h35, 3h35, 5h35, 8h35, 11h35, 14h35, 17h35, 20h35, 23h35 and 25h35 post mortem. The CRA analyzes were performed at the time of 25h35 post mortem. The pH measurements indicated that only from the 04 time (8h35 post mortem) was possible to verify an indicative of stabilization, being that PSE meat pH was 5,69±0,07, and normal meat was 5,93±0,09. The final pH (25h35 post mortem) was 5,98±0,06 and L* 57,30± 2,39 for normal meat, while for PSE meat the result was 5,72±0,06 and L* 59,44±1,51. To CRA, the average of the samples (67,19±3.13 and 64,45± 2.66) showed a difference between the normal chicken fillets and PSE respectively. The data found in this study are consistent with those reported by own research group in another slaughterhouse and contradicts similar works, but made at room temperature, indicating that for chickens under commercial conditions the resolution of rigor mortis occurs after 8h35 post mortem.